Apsuara – The Codex of Abkhazian’s Identity and its metamorphosis - Gvantseladze, Teimuraz (Actual Problems of Kartvelology, 2025)
There is a concept and a term expressing Abkhazian language - Apsuara, which means all the obligatory positive characteristics for any Abkhazian. In fact Apsuara is the identity codex for Abkhazians. In the work there is reconstructed the historical face of this codex, based on the old written sources and it is compared to the present Abkhazian identity.